Synthesis and Evaluation of Lung Tissue Retentive Prodrugs - Ayre, Jack (2022)
In the time of a global respiratory pandemic, there has never been a more pertinent time to improve the current medications responsible for relieving the symptoms of respiratory diseases such as COPD and Asthma. Administration of drugs directly to the site of action through the pulmonary drug delivery route can give significant benefits over other traditional routes of administration i.e. oral. Avoidance of first pass metabolism in the liver, reduced drug dosage and significant reduction of compound exposure to other organs, ultimately leading to fewer side effects, are all benefits of the pulmonary delivery route. However, rapid drug elimination from lung tissue into the pulmonary vein, combined with the pan antagonistic nature of receptor antagonists and heavy presence of muscarinic receptors in other tissues, often leads to increased side effects in other organs, such as the heart.